Assess the Reality of the Process of Applying the strategic Innovation In Business organizations : A prospective Study of comparative analysis in anumber of business organizations the Iraqi Industrial - محمد, بشرى هاشم (Journal of Economics and Administrative Sciences, 2013)
Abstract :      The research aims to Estimate the Strength of Strategic Innovation application in terms of application strength , and on the overall level in number of Iraqi Industrial business organizations . After wards determine whether their is differerences among those organizations in application process for the dimensions , and for the overall process .      The Research revealed number of conclusions including that the process of strategic innovation is applied in a good Level , and demonstrates the desier of the industrial companies Leaders to Launch beyond the familiar products , and to provide new products that satisfy customers, and meet their favourites .     The Research presents set of recommendations, including that the companies should seek increasing of the strategic innovation level, and adapt it as a philosophy of work , furthermore to take care of the new ideas and initiatives of the employees, and employ theme in order to enrich the competition process between companies within the same sector, then compete at the level of industrial sector companies generally .